Dentists’ Behavior of Preventive Measures toward COVID-19 transmission at Dental Clinics in Pekanbaru City - Oktavia Dewi; Nurlisis Nurlisis; M Reyhan (Journal of Social Science, 2021)
ackground Dentist professions are the greatest risk of being infected with Covid-19 virus. Dentists are very often exposed to bioaerosol, which is produced during dental work. There were 202 dentists in Indonesia who died due to exposure to the covid-19 virus. Dentists' behavior and attitude in dealing with the Covid-19 virus outbreak is very important in preventing transmission of the virus their practice room. This study aims to analyze the behavior of dentists to prevent covid transmission during dental treatment in the practice room. This research was a qualitative research with an exploratory approach. The research subjects were several dentists practicing independently in Pekanbaru City who were selected by purposive sampling. The data were collected by conducting in-depth interviews and incidental observations when the dentist performed treatment in the practice room. Data analysis was performed using the theme design and data validity test using source triangulation and data triangulation. All dentists have good knowledge and attitudes in preventing the transmission of covid-19, however, not all dentists have taken infection prevention measures because they have not used personal protective equipment (PPE) according to the standards recommended by the Indonesian Association of Dentists (PDGI) and Indonesian Doctor Association (IDI). This is due to inconvenience at work and limited costs. The behavior of preventing the transmission of covid-19 carried out by dentists in an independent practice room is not optimal. It is expected that dentists wear level 3 personal protective equipment and the government facilitates periodic swab checks and provides vaccinations.